Penpulimab for Relapsed or Refractory Classical Hodgkin Lymphoma: A Multicenter, Single-Arm, Pivotal Phase I/II Trial (AK105-201) - Song, Yuqin; Zhou, Keshu; Jin, Chuan; Qian, Zhengzi; Hou, Ming; Fan, Lei; Li, Fei; Ding, Kaiyang; Zhou, Hui; Li, Xiaoling; Chen, Bing; Sun, Xiuhua; et al. (Frontiers in Oncology, 2022)
Background: Nearly all anti-PD-1 antibodies are of the IgG4 isotype, and thus possess residual FcR effector functions. Such anti-PD-1 antibodies are also associated with immune tolerance and escape due to instability of the CH3 domain and Fc-Fc interaction. In this trial, we examined the efficacy and safety of penpulimab, a novel IgG1 anti-PD-1 antibody that does not bind to the Fc receptor, in patients with refractory or relapsed classical Hodgkin lymphoma (R/R cHL). Methods: Adult patients (≥18 years of age) with R/R cHL received 200 mg penpulimab once biweekly until disease progression or unacceptable toxicities for a maximum of 24 months. The primary endpoint was objective response rate (ORR) based on the Independent Radiology Review Committee per Lugano 2014 criteria. Secondary endpoints included progression-free survival (PFS), overall survival (OS), treatment-related adverse events (TRAEs) and immune-related adverse events (irAEs). Results: A total of 94 patients were enrolled. The median follow-up was 15.8 months. The ORR was 89.4% (95% CI 80.8%, 95.0%) in the full analysis set (85 patients). Forty (47.1%) patients achieved complete remission, 36 (42.4%) patients achieved partial remission. The 12-month PFS rate was 72.1% (95% CI 60.5%, 80.8%) and the 18-month OS rate was 100%. Totally 97.9% (92/94) of patients experienced at least one TRAE. The rate of grade 3 and above TRAEs was 26.6% (25/94). In addition, 51 (54.3%) patients experienced an irAE, and 4 (4.3%) patients developed grade 3 or above irAEs. No irAE-related death occurred. Conclusions: Penpulimab was effective and safe in patients with R/R cHL.